Respuesta :

Answer:

The answer is below

Step-by-step explanation:

Firstly, let us find the value of x. Multiply the first equation by a and the second equation by b to get:

a²x + aby = ca             (3)

b²x + aby = cb             (4)

Subtract equation 4 from equation 3 to get:

x(a² - b²) = c(a - b)

but a² - b² = (a + b)(a - b)

x(a + b)(a - b) = c(a - b)

x(a + b) = c

[tex]x=\frac{c}{a+b}[/tex]

Secondly, let us find the value of y. Multiply the first equation by b and the second equation by a to get:

abx + b²y = cb             (5)

abx + a²y = ca              (6)

Subtract equation 5 from equation 6 to get:

y(a² - b²) = c(a - b)

but a² - b² = (a + b)(a - b)

y(a + b)(a - b) = c(a - b)

y(a + b) = c

[tex]y=\frac{c}{a+b}[/tex]